Study of The Translation Expressions Of Love In The Book Thūq Al-Hamāmah (String Of Pigeon Necklaces) By Ibn Hazm Al-Andalusia: Kajian terjemahan ekspresi cinta dalam buku thu>q al-hama>mah (untaian kalung merpati) karya ibn hazm al-andalusi - Diva Kristya Ayunissa; Muhammad Yunus Anis (STAI Nurul Huda Kapongan Situbondo, 2023)
This study aims to examine: the expressions of love types, the translation techniques implemented in the expressions of love translation, and the quality of the translation of the expression of love in the book Thuq al-Hamamah (The Pigeon Necklace) by Ibn Hazm Al-Andalusi. The method used in this research is descriptive qualitative. Data collection techniques were carried out using observation, notes, questionnaires, and interviews. The results of the study show that the components of expression of love are intimacy, passion, and commitment. The 13 translation techniques types are discursive creation, common equivalent, linguistic compression, reduction, compensation, amplification, particulation, generalization, modulation, transposition, linguistic amplification, literalization, and borrowing. The quality of the resulting translation is included in the type of legibility with a score of (36%), acceptable (40%), and less accurate (24%). The use of discursive creation techniques is the main factor influencing the value of accuracy on the quality of translation